Competitive and Equitable Compensation: Can You Have Both?. (September 2018) - Greene, Robert J.
Ensuring compensation policies and programs are viewed by employees as equitable, competitive and appropriate enables an organization to make their value proposition attractive to the talent it needs to succeed. There is significant controversy today related to the wage and wealth gap, and wage inequality is widely viewed as unfair and unwarranted. Each compensation strategist must reconcile business needs with the needs of the workforce, and altering the manner in which available resources are allocated can work toward that reconciliation. Alternative approaches for doing so are presented.